Family Forerunners? Parental Separation and Partnership Formation in 16 Countries. Issue 1 (1st May 2020) - Härkönen, Juho; Brons, M.D. (Anne); Dronkers, Jaap
Abstract: Objective: To analyze the relationships between parental separation and partnership formation patterns across 16 countries and over time, and how the relationships are shaped by contextual factors. Background: Several studies have found that parental separation predicts higher rates of cohabitation and lower rates of marriage. Few studies have analyzed these relationships over time or across countries, and none have systematically analyzed whether they are moderated by contextual factors. Method: Retrospective partnership histories on 138, 739 women and men from the Generations and Gender Survey and Harmonized Histories datafiles were used. Monthly data on entry into cohabitation or marriage as the first coresidential union, and on entry into marriage were analyzed using life table and event history techniques. The overall incidences of parental separation and of premarital cohabitation were used as contextual‐level measures in the event history analyses. Results: The association between parental separation and partnership formation was moderated by the spread of premarital cohabitation. Higher incidence of cohabitation was associated with a weaker positive association between parental separation and cohabitation, and a more negative association between parental separation and marriage. The associations between parental separation and partnership formation were not weaker when parental separation was more common. Conclusion: Children of divorce have been among the forerunners of the increase in cohabitation and the retreat from marriage.